Um jornal entre Brasil e Japão : a construção de uma identidade para japoneses no Brasil e brasileiros no Japão - Silva, Victor Hugo Martins Kebbe da (Universidade Federal de São Carlos, 2008)
The present inquiry will survey the study of the japanese-brazilian identity referent to the Japanese descendants born in Brazil - the "nikkeis", as in the ways this group is conceived, as much for the descendants residents in Brazil as for all those immigrating to Japan in pursuit of economic and financial ascension, as the Dekasseguis. In this migratory flow we detect the classic categories, as the identity, ethnicity, race and State, don t consider all dimensions of the new problems originated from the fact descendants think in a common identity, surpassing politics, economics and culturally the national barriers. Therefore, I make use as base to this study the Nippo-Brasil Journal and the Made In Japan magazine, representative publications of the nikkei community, which served as privileged access method to the way how these descendants think themselves, having as angle the Japanese Immigration Centenary in Brazil, celebrated in 2008. Firstly seen as a social drama, it is possible to notice by the immigration centenary, besides representing a historical mark in Japanese immigration, it also represents a momentum in which the social structure, dilemmas, moral dictates are revealed, therefore being a relevant investigative device.
Keywords: Antropologia urbana; Migração do Japão para o Brasil; Identidade nipo-brasileira; Brasil Japão emigração dekassegui; Transnacionalismo; CIENCIAS SOCIAIS APLICADAS